2022
DOI: 10.1007/s40262-022-01126-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacodynamics, and Pharmacokinetics of P2X3 Receptor Antagonist Eliapixant (BAY 1817080) in Healthy Subjects: Double-Blind Randomized Study

Abstract: Background and Objective There is no licensed treatment for refractory chronic cough; off-label therapies have limited efficacy and can produce adverse effects. Excessive adenosine triphosphate signaling via P2X3 receptors is implicated in refractory chronic cough, and selective P2X3 receptor antagonists such as eliapixant (BAY 1817080) are under investigation. The objective of the study was to investigate the safety and tolerability of ascending repeated oral doses of eliapixant in healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 57 publications
4
15
0
Order By: Relevance
“…The first postdose taste tests were administered 3 hours postdosing, which was within 1 SD of t max under fasted conditions, or very close to t max under fed conditions, yet there was no clear difference in response compared with the baseline tests. Findings from the proof‐of‐concept studies with eliapixant, which commenced following the research described here, are consistent with these early observations that eliapixant appears to have fewer taste‐related AEs than observed with nonselective P2X3 and P2X2/3 receptor antagonism 13–17,25,26 . A multiple‐dose PK study of eliapixant 10–750 mg in healthy volunteers showed no clinically relevant effects on taste perception, in addition to a less than dose‐proportional increase in exposure with increasing dose 25 .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The first postdose taste tests were administered 3 hours postdosing, which was within 1 SD of t max under fasted conditions, or very close to t max under fed conditions, yet there was no clear difference in response compared with the baseline tests. Findings from the proof‐of‐concept studies with eliapixant, which commenced following the research described here, are consistent with these early observations that eliapixant appears to have fewer taste‐related AEs than observed with nonselective P2X3 and P2X2/3 receptor antagonism 13–17,25,26 . A multiple‐dose PK study of eliapixant 10–750 mg in healthy volunteers showed no clinically relevant effects on taste perception, in addition to a less than dose‐proportional increase in exposure with increasing dose 25 .…”
Section: Discussionsupporting
confidence: 84%
“…Findings from the proof-of-concept studies with eliapixant, which commenced following the research described here, are consistent with these early observations that eliapixant appears to have fewer tasterelated AEs than observed with nonselective P2X3 and P2X2/3 receptor antagonism. [13][14][15][16][17]25,26 A multiple-dose PK study of eliapixant 10-750 mg in healthy volunteers showed no clinically relevant effects on taste perception, in addition to a less than dose-proportional increase in exposure with increasing dose. 25 Furthermore, in a phase II study, eliapixant was well tolerated in patients with RCC, with a lower incidence of taste-related AEs (8-21% of patients) 26 than has previously been reported for gefapixant (up to 80% of patients with 50 mg twice daily) in RCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,28 In healthy volunteers, the eliapixant plasma levels predicted to achieve $80% P2X3 receptor occupancy, the predicted therapeutic threshold, were reached with doses of 200 mg and 750 mg BID. 23 In a phase 2a study assessing eliapixant 50, 200, and 750 mg BID (the same formulation as used in the healthy volunteer studies) in patients with RCC, an efficacy plateau appeared to be reached at 200 mg BID for the primary endpoint of cough frequency, whereas the subjective endpoints continued to improve at the 750 mg dose. 31 In the phase 2b PAGANINI study in patients with RCC, which used the same formulation as PUCCINI (25 mg, 75 mg, and 150 mg BID), an efficacy plateau effect was observed with the 75 mg BID dose group.…”
Section: Aes N (%)mentioning
confidence: 99%
“…The eliapixant 150 mg BID dose was chosen based on previous studies in healthy volunteers, which used a different formulation to that used in PUCCINI, where a 750 mg dose was approximately equivalent to the 150 mg dose used in PUCCINI for bioavailability. 23,28 In healthy volunteers, the eliapixant plasma levels predicted to achieve $80% P2X3 receptor occupancy, the predicted therapeutic threshold, were reached with doses of 200 mg and 750 mg BID. 23 In a phase 2a study assessing eliapixant 50, 200, and 750 mg BID (the same formulation as used in the healthy volunteer studies) in patients with RCC, an efficacy plateau appeared to be reached at 200 mg BID for the primary endpoint of cough frequency, whereas the subjective endpoints continued to improve at the 750 mg dose.…”
Section: Aes N (%)mentioning
confidence: 99%